THE RIGHTS AND OBLIGATIONS OF THE PARTICIPATORS OF THE TAX PAYING, TAX COLLECTING AND FORCED TAX COLLECTING PROCEDURES APPLIED IN THE INTERWAR LITHUANIA - Burneikaitė, Indra (Teisė, 2017)
The performed analysis shows that there was a lack of more detailed substatutory legal regulation in the interwar Lithuania determined in the area of tax paying and tax collecting. Therefore, taxpayers could be misled by state institutions that applied different procedures for collecting taxes. Provided that the regulation of tax paying and tax collecting procedures could not prevent tax inspectors from abuse of authority, it was subject to improve. The legal regulation of the interwar Lithuania restricted the possibility of taxpayers to appeal against actions of tax inspectors in the area of forced tax collecting more than it should. The main reason that caused this problem was the fact that disputes over illegal acts of officers of state authorities, who carried out the forced tax collecting procedure, could not be taken to the courts. Considering this, legal regulation in this area was subject to improve as well. In the practice of the Lithuanian Supreme Tribunal, the cases where officers of state authorities failed to fulfill their procedural obligations in the court were treated indulgently, consequently, unnecessarily complicating the possibilities of taxpayers to defend their rights in the courts of the interwar Lithuania in the area of forced tax collecting.